Processes controlling programmed cell death of root velamen radicum in an epiphytic orchid - Li, Jia-Wei (Ann Bot, 2020)
BACKGROUND AND AIMS: Development of the velamen radicum on the outer surface of the root epidermis is an important characteristic for water uptake and retention in some plant families, particularly epiphytic orchids, for survival under water-limited environments. Velamen radicum cells derive from the primary root meristem; however, following this development, velamen radicum cells die by incompletely understood processes of programmed cell death (PCD). METHODS: We combined the use of transmission electron microscopy, X-ray micro-tomography and transcriptome methods to characterize the major anatomical and molecular changes that occur during the development and death of velamen radicum cells of Cymbidium tracyanum, a typical epiphytic orchid, to determine how PCD occurs. KEY RESULTS: Typical changes of PCD in anatomy and gene expression were observed in the development of velamen radicum cells. During the initiation of PCD, we found that both cell and vacuole size increased, and several genes involved in brassinosteroid and ethylene pathways were upregulated. In the stage of secondary cell wall formation, significant anatomical changes included DNA degradation, cytoplasm thinning, organelle decrease, vacuole rupture and cell wall thickening. Changes were found in the expression of genes related to the biosynthesis of cellulose and lignin, which are instrumental in the formation of secondary cell walls, and are regulated by cytoskeleton-related factors and phenylalanine ammonia-lyase. In the final stage of PCD, cell autolysis was terminated from the outside to the inside of the velamen radicum. The regulation of genes related to autophagy, vacuolar processing enzyme, cysteine proteases and metacaspase was involved in the final execution of cell death and autolysis. CONCLUSIONS: Our results showed that the development of the root velamen radicum in an epiphytic orchid was controlled by the process of PCD, which included initiation of PCD, followed by formation of the secondary cell wall, and execution of autolysis following cell death.